Settlement finality as a public good in large-value payment systems - Henri Pagès; David Humphrey (European Central Bank (ECB), 2005)
Target is a real time gross settlement (RTGS) large value payment network operated by European central banks that eliminates systemic risk. Euro1 is a privately operated delayed net settlement (DNS) network that reduces substantially systemic risk but does not eliminate it. This difference makes RTGS networks more expensive to users even if both networks had the same unit operating costs. This provides an incentive for users to shift payments to the more risky network in normal times and back to Target in times of financial market disruption. The estimated extra cost to a DNS network from posting collateral sufficient to cover all exposures (and eliminate systemic risk) is from 15 to 42 cents per transaction. If full cost recovery on an RTGS system were reduced by this amount, user collateral costs but not risks would be equalized between networks. Full collateralization on DNS networks equalizes both user costs and risks.
Keywords: E58; G15; H23; H41; 330; payments; public good; settlement; Zahlungsverkehr; Öffentliche Güter; Eurozone; EU-Staaten